Repairing the medial meniscus posterior root during open-wedge high tibial osteotomy does not significantly affect clinical outcomes - Dong, Conglei; Kong, Lingce; Niu, Yingzhen; Dong, Jiangtao (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to evaluate the effectiveness of medial meniscus posterior root tear (MMPRT) repair during open-wedge high tibial osteotomy (OWHTO) by investigating MMPRT healing and clinical outcomes. It also aimed to explore the impact of lower limb alignment correction on MMPRT healing in unrepaired cases.MethodsA total of 157 patients (68 males and 89 females) were included, with an average age of 57.0 ± 6.66 years and an average postoperative follow-up duration of 22.1 ± 2.92 months, who underwent OWHTO followed by second-look arthroscopy. Patients were divided into two groups: the OWHTO with MMPRT repair group (n = 82) and the OWHTO-only group (n = 75). Each group was further divided into Fujisawa subgroup and neutral subgroups to assess the healing of MMPRT and clinical outcomes.ResultsThe overall MMPRT healing outcomes in the OWHTO with MMPRT repair group were similar to the OWHTO-only group. Cartilage damage showed no intergroup differences. Functional improvements were equivalent between groups. Subgroup analyses revealed differential outcomes: Fujisawa subgroup exhibits superior healing in isolated OWHTO, but not in combined procedures.ConclusionMid-term clinical outcomes were comparable between OWHTO combined with MMPRT pull-out repair and isolated OWHTO. For patients undergoing isolated OWHTO, mechanical axis correction targeting the Fujisawa point is significantly more conducive to MMPRT healing than neutral alignment. Consider prioritizing MMPRT repair for young patients or those with high activity demands. When MMPRT repair is not performed, it is recommended to target the correction of knee alignment to the Fujisawa point.